On the fracture toughness study of Singapore MRT rails with 3D edge cracks : multiple cracks behaviours of the railway wheel due to cyclic rolling contact - Myat, Noe Oo (2019)
Safety is the most important thing in our lives. This research could play as a vital role in the safety of the railway wheel. Since many years ago, a lot of researches have been studied for crack growth in railway wheel to prevent the major failure that leads to accidents. There are different types of defects that occur in the railway wheels. Nowadays, there are various kinds of models to analyze the multiple cracks behaviours of the railway wheel due to cyclic rolling contact. By using software ABAQUS Version 6.13, Extended Finite Element Method (XFEM) can be performed to test for different simulations. Cracks often initiate in the white etching layer (WEL) and then propagate into the wheel due to cyclic rolling contact. The cracked material may break away from the railway wheel, leaving voids know as spalling. Spalling of WEL could be evaluated by rolling contact fatigue (RCF) test and finite element analysis (FEA). WEL remarkably reduces the RCF life of wheel. In this report, I built a 2D spalling model with two cracks by using ABAQUS software. Then, I applied cyclic rotation on rail. Finally, from the results, I investigated the cracks interaction in WEL materials.